2012
DOI: 10.1097/mpg.0b013e3182323c75
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam‐Ketamine Combination for Moderate Sedation in Upper GI Endoscopy

Abstract: Our data suggest that synergistic sedation with oral ketamine and IV midazolam for UGIE in children is a suitable and safe sedation. The higher rate of vomiting in group B in contrast to previous studies must be caused mainly by the oral route of ketamine administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
0
25
1
Order By: Relevance
“…In the meta-analysis carried out, although side effects occurred in 30% of the adults, they only occurred in 1.4% of the children 31. The incidence of emergence reactions increases, especially when ketamine is used at high doses, when a fast injection (<1 minute) is administered and when excessive visual or verbal stimuli exist during the recovery 2,4. In our previous study, we used 0.5 mg/kg ketamine and the emergence reaction was 1.2%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the meta-analysis carried out, although side effects occurred in 30% of the adults, they only occurred in 1.4% of the children 31. The incidence of emergence reactions increases, especially when ketamine is used at high doses, when a fast injection (<1 minute) is administered and when excessive visual or verbal stimuli exist during the recovery 2,4. In our previous study, we used 0.5 mg/kg ketamine and the emergence reaction was 1.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Vomiting occurs more often in gastrointestinal tract procedures than in other processes. Motamed et al 4 reported that vomiting occurred in 17.6% of the children who underwent UGE procedures. Some studies have reported that administration of atropine along with ketamine sedation reduces vomiting, but there is no consensus on this issue 3739.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study comparing midazolam-ketamine, midazolam-placebo and midazolam-fentanyl, dizziness, vomiting and cough were most frequently observed in the midazolam-ketamine group and a significant difference was observed between the midazolam-ketamine group and the midazolam-fentanyl group in terms of diplopia and vomiting ( p =0.004 and 0.002, respectively) [19]. …”
Section: Discussionmentioning
confidence: 99%
“…To prevent or reduce these complications, other analgesic medications can be used in place of fentanyl (2, 3, 16). Studies have shown that the combination of ketamine and propofol can effectively prevent deep sedation of patients and cause lower postoperative nausea and vomiting, more stable hemodynamics, and a shorter discharge time after ERCP (11, 12, 16-18). …”
Section: Introductionmentioning
confidence: 99%